Effect of elevated levels of uric acid on thrombocyte hemostasis in patients with hypertonic disease of stage ІІ - Valigura, Maria (Journal of Education, Health and Sport, 2018)
The effect of uric acid on the functional activity of platelets in patients with hypertension, hyperuricemia, and a combination of these two conditions was studied. In the study, 75 patients were examined: 15 physically healthy subjects (control group), 17 patients with hyperuricemia without hypertension (group I), 23 patients with hypertension and hyperuricemia (group II) and 20 patients with isolated hypertension 2 stages (group III). In order to study thrombocyte hemostasis, estimates of spontaneous platelet aggregation and induced aggregation with adenosine diphosphate (ADP), arachidonic acid (AA), collagen and epinephrine were performed. An assessment of endothelium dependent vasodilatation was also performed on Celermajer cuffs. Hyperuricemia was diagnosed with uric acid levels > 420 μmol / L. In the course of the investigation, we determined that patients with hypertension, hyperuricemia and their combination observed an increase in the functional activity of the platelets, which manifests itself in an increase in the degree of spontaneous aggregation, a significant activation of platelet aggregation induced by arachidonic acid and collagen. Hyperagracy was detected in all hypertension patients and was more pronounced in patients with hypertension with concomitant hyperuricemia and was dependent on uric acid levels in plasma.